Subjective Rights in the Light of the Reform on Public Servitudes - T. S. Krasnova (Теоретическая и прикладная юриспруденция)
The article is dedicated to the results of the land law reform which was carried out in 2018, namely the introduction of updated provisions on public servitudes to the Land Code of the Russian Federation. It can be argued that today in the Land Code of the Russian Federation there are rules on two types of public servitudes — for benefit of any number of unspecified persons (art. 23) and in favour of certain entities (Ch. V.7). Both types of public servitudes are established in accordance with the Land Code of the Russian Federation, i. e. the provisions of the Civil Code of the Russian Federation are inapplicable to the legal relations arising in connection with establishment, implementation and termination of public servitudes. In this context the question on the legal nature of public servitudes arises. In particular are public servitudes subjective property rights? The author of the article offers answers to this and some other questions.